Hypophosphatemia is Prevalent among Preterm Infants Less than 1,500 Grams - Al-Wassia, Heidi; Lyon, Andrew W.; Rose, Sarah M.; Sauve, Reginald S.; Fenton, Tanis R. (American Journal of Perinatology, 2019)
Objective This article identifies the prevalence and associated factors of hypophosphatemia (HP) in very low birth weight (VLBW) infants in the first week of life.Study Design Prospective exploratory cohort study of 106 consecutive VLBW infants admitted to neonatal intensive care at Foothills Hospital, Calgary, Canada. HP was defined as at least one measurement of serum phosphate < 1.5 mmol/L (4.5 mg/dL).Results Seventy-seven percent (82/106) of the VLBW infants had HP, with significantly higher prevalence in infants < 1,000 g (94%) compared to infants ≥ 1,000 g (61%) (p < 0.001). Hypophosphatemic infants had lower birth weight (p < 0.001), gestational age (p < 0.001), and their increase in phosphate intake was slower (p = 0.003). Respiratory distress syndrome (RDS) (p = 0.002), intraventricular hemorrhage (IVH) ≥ grade III (p = 0.020), and hyperglycemia (p = 0.013) were more frequent among hypophosphatemic infants, especially among those < 1,000 g. Mortality, seizures, arrhythmias, and need for transfusion were not different between groups. Birth weight modified the association between RDS, IVH, hyperglycemia, and HP.Conclusion HP was ubiquitous among infants < 1,000 g and highly prevalent among those weighing 1,000 to 1,500 g. While the direction of effect was not clear, RDS, IVH, and hyperglycemia were associated with HP. Prevention of HP in these physiologically immature neonates might improve neonatal outcomes.
Keywords: hypophosphatemia; very low birth weight; risk factors; preterm infants